Lesões macroscópicas e histológicas na cavidade nasal de cães e gatos submetidos à necropsia - Marcus, Valentina Berté (2025)
The nasal cavity of dogs and cats constantly faces challenges to its homeostasis due to various etiologies that can trigger nonspecific clinical signs. Few studies investigate nasal cavity lesions in asymptomatic animals. This work aimed to analyze the nasal cavity of dogs and cats for histological alterations, comprising two prospective studies. The first study sought to evaluate the nasal cavity of dogs and cats undergoing necropsy without a history of respiratory disease to identify common morphological changes. A total of 81 animals were selected, including 54 dogs and 27 cats. For each case, nasal turbinates were collected from six different points (three in each hemisphere of the cavity) for histological analysis. Lesions of varying degrees were observed in 67 out of 81 animals, 48/67 dogs and 19/67 cats. Histopatologic findings demonstrate that lymphoplasmacytic rhinitis (45/67) was the most prevalent alteration in both species. In dogs, ulcers and erosions (4/48) and oronasal fistulae (2/48) were the second and third most prevalent alterations, although uncommon. In cats, neutrophilic rhinitis was the second most frequent alteration (5/19). The findings of this study demonstrate that even healthy animals exhibit nasal cavity alterations and provide veterinarians with insights to better interpret the clinical significance of lesions identified during rhinoscopies. The objective of the second study was to characterize the anatomy, histology, and histochemical aspects of the lateral nasal gland in dogs and cats. Research on this structure is both old and scarce, with little focus on its histology and no reports of pathologies affecting these glands in dogs and cats. The lateral nasal gland was collected from dogs and cats undergoing necropsy in 2023, totaling 98 cases (64 dogs and 34 cats). The glands were located in the maxillary recesses of all animals after the removal of the nasal turbinates. Macroscopically, the glands appeared as flat, rounded structures with a thicker central portion and a coloration similar to the mucosa. Histologically, they were composed of acinar structures formed by granule-filled cells organized into lobules, supported by fibrovascular stroma. In the center of each lobule, a small (intercalated) duct was observed, which drained into larger (striated) ducts. The only primary alteration observed in the lateral nasal gland was a unilateral adenocarcinoma in an elderly cat, representing the first reported neoplasm affecting these structures. The findings of this study are significant as they highlight the existence of this gland. Recognizing these intranasal structures is important for detecting primary lesions affecting these glands, whether through rhinoscopy, advanced imaging, or necropsy. It is hoped that the two articles presented in this dissertation will aid veterinary clinicians and pathologists in diagnosing and interpreting nasal diseases in dogs and cats.